Anticipation and Mechanisms for Resolving Interethnic Conﬂicts - A. I. Kugay; I. V. Zakharova (Управленческое консультирование, 2021)
The formation of a harmonious environment that promotes personal development is a necessary component for each person and for the functioning of the community, regardless of the form of its political structure. Creating a harmonious environment includes, among other things, working to maintain a positive inter-ethnic environment. To do this, it is necessary to conduct constant monitoring and work to support a harmonious inter-ethnic background. The article deals with the peculiarities of the inﬂuence of immersion in the interethnic environment and self-determination in the community on the individual, the inﬂuence of the communicative connection between representatives of diﬀerent ethnic groups on the functioning of the community.